Nutrient composition in berries of promising cultivars and elite seedlings of Ribes L. - M. Yu. Akimov; E. V. Zhbanova; T. V. Zhidekhina; A. M. Mironov; O. S. Rodyukova (Труды по прикладной ботанике, генетике и селекции)
Background. Black and red currant berries are high-vitamin dietary products and important raw materials for healthy food production.   Materials and methods. Berries collected from promising cultivars and elite seedlings of black and red currant from the genetic collection of the I.V. Michurin Federal Science Center were analyzed. Chemical composition and total antioxidants were assessed in 2017–2022 with analytical instruments at the Biochemistry and Food Technology Laboratory according to standardtechniques.   Results and discussion. Berries of the studied black currant genotypes accumulated 16.3 % Brix of soluble solids, 10.0 % of sugars, 2.47 % of organic acids, 117.3 mg/100 g of vitamin C, and 201.4 mg/100 g of anthocyanins. Black currant cv. ‘Aksinya’ was the best in chemical composition (the long-term average sugar content was 13.3 %, organic acids amounted to 1.97 %, vitamin C to 156.7 mg/100 g, and anthocyanins to 257.4 mg/100 g) and manifested high antioxidant properties (92.4 mg/100 g of gallic acid). Red currant berries contained 12.0 % Brix of soluble solids, 7.7 % of sugars, 1.69 % of organic acids, 34.0 mg/100 g of vitamin C, and 57.3 mg/100 g of anthocyanins. Red currant cv. ‘Gazel’ and elite seedling 30-7-58 were identified for more than 40 mg/100 g of vitamin C in their berries, while elite seedling 27-13-42 had the highest amount of anthocyanins (above 100 mg/100 g) and high antioxidant properties (45.7 mg/100 g of gallic acid). The identified sources are recommended for fresh consumption, functional food production, and further breeding efforts.